Peningkatan Kesadaran Quarter Life Crisis Pada Mahasiswa Pendidikan Islam Melalui Edukasi Lingkungan Sosial - Restyani, Dilla (Jurnal Dedikasi Pengabdian Pendidikan, 2025)
Quarter Life Crisis (QLC) is a psychological phenomenon that commonly occurs in early adulthood, including college students, and is characterized by confusion, social pressure, and anxiety about the future. Students of the Islamic Religious Education (PAI) Study Program are a vulnerable group to QLC, primarily if a healthy social environment does not support them. This activity aims to increase student awareness of the importance of building a positive social environment when facing the challenges of adult transition. The implementation of the activity was carried out in the form of psychoeducation based on the results of quantitative correlational research on 111 PAI students at the Islamic University of Riau. The study showed that the social environment significantly influences QLC with a significance value of 0.001, an influence contribution of 52.5% (moderate category), and a strong correlation of 72.5%. These results are the basis for implementing educational activities through group discussions, social reflection, and independent counseling to increase students' adaptability to environmental dynamics. Thus, this activity is expected to be able to strengthen students' mental readiness and form a collective awareness of the importance of social support in facing QLC.